2016
DOI: 10.1016/j.antiviral.2016.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Novel diversity-oriented synthesis-derived respiratory syncytial virus inhibitors identified via a high throughput replicon-based screen

Abstract: Respiratory syncytial virus (RSV) infections affect millions of children and adults every year. Despite the significant disease burden, there are currently no safe and effective vaccines or therapeutics. We employed a replicon-based high throughput screen combined with live-virus triaging assays to identify three novel diversity-oriented synthesis-derived scaffolds with activity against RSV. One of these small molecules is shown to target the RSV polymerase (L protein) to inhibit viral replication and transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…180,182 The Pictet-Spengler-derived spirocycles 40 and 44 show antimalarial and antiviral activity, respectively. 178,183 Other compounds shown are described in more detail in the vignettes in the main text. Properties relevant to their value as probes are discussed in Box 2.…”
Section: Figure 1 |mentioning
confidence: 99%
“…180,182 The Pictet-Spengler-derived spirocycles 40 and 44 show antimalarial and antiviral activity, respectively. 178,183 Other compounds shown are described in more detail in the vignettes in the main text. Properties relevant to their value as probes are discussed in Box 2.…”
Section: Figure 1 |mentioning
confidence: 99%
“…Our initial characterization of the AVG-233 class revealed that the inhibitor does not block phosphodiester bond formation per se but disturbs initiation of viral RNA synthesis at the promoter ( 24 ). This inhibition pattern may reflect pharmacological interference with a predicted conformational rearrangement of the polymerase complex during initiation ( 43 , 44 ). Three lines of experimental evidence support this view: the AVG class resistance profile, the mechanism of action (MOA) characterization in biochemical RdRP assays, and the photoaffinity labeling–based mapping of the target site.…”
Section: Discussionmentioning
confidence: 99%
“…BRD3969 (19-2) was shown to inhibit viral replication, no RSV-B subtype activity was observed. 24 The BRD9259 (19-3) scaffold type, however, did show activity against both subtypes but was less explored in terms of published SAR. (T1-3).…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…This system has had SH, G, and F proteins removed and replaced by an antibiotic resistance selection marker . They described the use of this screen against the AstraZeneca million compound library but reported no tractable hits. , A subsequent collaboration with the Broad Institute (Cambridge, MA) described the screening of the Broad Institute diversity oriented synthesis library and subsequent filtering of hits using whole virus CPE assays with both RSV-A and RSV-B subtypes . In addition, the Broad/AstraZeneca team utilized a transient minigenome assay, a system that contains only proteins necessary for replication and can be engineered to allow uncoupling of replication and transcription. , The output from this screen is discussed later (section ).…”
Section: The Rsv Small-molecule Discovery Processmentioning
confidence: 99%
See 1 more Smart Citation